Psychological Skill Training in Sports - Miçooğulları, Bülent Okan (Academician Publishing Book DOI Portal, 2023)
This book is a study on sports psychological skill training for young basketball players. The author examines the methods and techniques used to improve athletes’ psychological skills. The book discusses strategies used to enhance athletes’ mental resilience, motivation, focus, and stress management. Additionally, it provides information on techniques used to increase athletes’ self-confidence and performance. In this book, the author presents the most effective methods used to improve the psychological skills of young basketball players.